2003
DOI: 10.1088/0741-3335/45/5/306
|View full text |Cite
|
Sign up to set email alerts
|

Generation of multiply charged ions at low and high laser-power densities

Abstract: The PERUN and PALS iodine laser systems and a Nd : YAG laser have been used for studies of ions emitted from various single element laser plasmas, at both low (I L ∼ 10 9 W cm −2 ) and high (I L ∼ 10 16 W cm −2 ) laser intensities. Sufficiently high current densities of low-charge ions, with energies only of hundreds of electronvolt, were produced for starting tests of a considered new hybrid ion source, based on coupling of laser ion source to electron cyclotron resonance plasma. Highly charged ions with char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 60 publications
0
27
1
Order By: Relevance
“…Refs. [18,19]). It has been shown that the distribution of ions over the charge states depends on the laser intensity and shifts to higher charges for higher intensity [19].…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [18,19]). It has been shown that the distribution of ions over the charge states depends on the laser intensity and shifts to higher charges for higher intensity [19].…”
Section: Introductionmentioning
confidence: 99%
“…These ions form a fast ion group, as opposed to the thermal, slower ion group accelerated by thermokinetic forces. The mechanism of acceleration using the double-layer in plasma corona dominates in the case of long driving pulses [7][8][9][10], but it can be also efficient in the case of short pulses of relatively low contrast (producing sufficiently thick underdense preplasma layer) [44,45]. Both the double-layer and S-LPA mechanisms were demonstrated to be efficient in generation backward-emitted heavy ion beams.…”
Section: Generation Of Highly Charged Heavy Ion Beamsmentioning
confidence: 99%
“…Studies of laser-driven generation of highly charged ions with the use of long-pulse (ns or subns) lasers have a much longer history and have been performed by several research groups [7][8][9][10][52][53][54][55][56][57][58]. Some results obtained by the Czech-Polish group with the use of subns high-energy iodine lasers are presented in Table 3 [10].…”
Section: Generation Of Highly Charged Heavy Ion Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, at the Plasma Asterix Laser System (PALS) Laboratory of Prague, for example, by using a pulsed laser at a fluence of 300 kJ/cm 2 , 400 ps pulse width, to irradiate tantalum in vacuum, the ion charge state distribution shown in Figure 6(b) [13] has been obtained. This distribution is very wide and it indicates a very high ion charge state production, up to 58 + , showing three ion charge state regions.…”
Section: Downloaded By [Northeastern University] At 06:20 25 Novembermentioning
confidence: 99%